2019
DOI: 10.26434/chemrxiv.9923642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sulfur- and Nitrogen-Containing Porous Donor-Acceptor Polymers as Real-Time Optical and Chemical Sensors

Abstract: Fully aromatic, organic polymers have the advantage of being composed from light, abundant elements, and are hailed as candidates in electronic and optical devices “beyond silicon”, yet, applications that make use of their π-conjugated backbone and optical bandgap are lacking outside of heterogeneous catalysis. Herein, we use a series of sulfur- and nitrogen-containing porous polymers (SNPs) as real-time optical and electronic sensors reversibly triggered and re-set by acid and ammonia vapors. Our SNPs incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Testing of multiple batches as well as multiple runs on the same batch confirmed the activity of the best-performing material, TT-TAB, within a 15% error margin, as is typically observed for batchbased photocatalytic hydrogen evolution testing (Figure S14). [30] Application of the same conditions to our previously reported sulfur-and-nitrogen-based polymer networks (SNPs) [2,16] showed that for these materials, triethanolamine and triethylamine afford higher activities than L-ascorbic acid (Figure S12). This behaviour seems at first surprising given that acidic media tends to favor proton reduction by enhancing donor-acceptor interactions between protonated triazines and sulfur-containing donors in SNPs.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Testing of multiple batches as well as multiple runs on the same batch confirmed the activity of the best-performing material, TT-TAB, within a 15% error margin, as is typically observed for batchbased photocatalytic hydrogen evolution testing (Figure S14). [30] Application of the same conditions to our previously reported sulfur-and-nitrogen-based polymer networks (SNPs) [2,16] showed that for these materials, triethanolamine and triethylamine afford higher activities than L-ascorbic acid (Figure S12). This behaviour seems at first surprising given that acidic media tends to favor proton reduction by enhancing donor-acceptor interactions between protonated triazines and sulfur-containing donors in SNPs.…”
mentioning
confidence: 78%
“…[2,5,[9][10][11][12] Aromatic amines can be used to incorporate the larger heptazine (C6N7) core via nucleophilic substitution to yield N-bridged donoracceptor systems, [13][14][15] but only the triazine core has been directly cross-coupled via carbon-carbon bond formation to yield highly photoactive materials. [2,16] Recently, sulfone oxides were introduced as electron acceptors for hydrogen evolution photocatalysts. The sulfone oxides serve dual functions as electron acceptors while improving the wettability of the aromatic polymer backbone for enhanced catalyst-substrate interaction.…”
mentioning
confidence: 99%
“…Optical technology shows distinct superiority in real-time sensing in numerous applications, such as chemical sensing and biosensing [ 10 , 11 , 12 ]. Especially, optical sensors based on surface plasmon resonance (SPR) have played a non-negligible role in the area of chemical sensing, foodborne marker screening, environmental monitoring and medical diagnostics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, donor and acceptor polymers (D-APs) have been extensively studied due to their wide range of potential applications in organic solar cells (Facchetti, 2013), light emitting diodes (Thompson et al, 2005), sensors (Kochergin et al, 2019), energy conversion (Gao et al, 2016), and storage devices (Guo, Li, Yu, Perepichka, & Meng, 2017). Thus, many synthetic strategies, mainly based on chemical modification, have been developed with the aim to diversify the properties and to achieve a higher versatility for this type of materials (Davis et al, 2017;Deng & Doyle, 2016;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%